Frailty in Older Adults: A Case Study - องค์มีเกียรติ ธัญยรัชต์ (Journal of Thailand Nursing and Midwifery Council, 2018)
This article presents an analysis of a case study of frailty in older adults dwelling in community. The analysis was based on a review of literature concerning the defnition of frailty, screening and diagnosis, risk factors, and management of frailty in older adults. According to the analysis presented herein, the article proposes that nurses should serve as case managers and nurse-led interdisciplinary team specialists to properly manage this condition. Frailty is a common geriatric syndrome that is not caused by usual degenerative conditions. It results in inability to cope with stress and could cause such undesirable outcomes as diseases, disabilities, and physical, psychological, and social vulnerabilities, leading to frequent hospitalization, high health expenditure and medical expense per capita, and increased mortality rate. Frailty can be prevented if health is promoted and restored before the onset of disability. Screening of frailty in older adults, which is performed using various multidimensional instruments, is based upon the presence of three or more of fve phenotypes, namely, muscle weakness, walking at an unusually slow pace, low level of physical activities, exhaustion, and unintentional weight loss. Regarding the present case study, frailty was found amongst illiterate, older female aged higher than 80 with low socio-economic status and insuffcient income, who had three or more underlying diseases, used four or more medications, received little support from their family or community, pursued unhealthy lifestyle, and lived in environments neither physically nor socially friendly to older adults. The gerontological nurses play an important part of nurse-led role in coordinating effcient management on risk factors that contribute to physical, psychological, and environmental aspects, in order to prevent or delay frailty or reduce its severity.